5-fluorouracil release from sunflower pectin hydrogels in simulated intestinal medium and its corresponding anti-carcinogenic activity - Çakır, Bilal; Gülseren, İbrahim; Çakır, Bilal; Gülseren, İbrahim (Association of Indian Pharmacist, 2017)
5-fluorouacil (5-FU) is a commonly used medication in the treatment of cancers including colon, stomach, pancreatic and breast cancers. In this study, 5-FU was encapsulated in low methoxyl sunflower pectin (i.e., sunflower LMP) hydrogel beads in order to investigate the potential of sunflower pectin in the delivery of cancer drugs. Calcium pectate beads were prepared using an extrusion dripping method. Dissolution kinetics were monitored in simulated intestinal fluid (SIF) medium and the dissolved fractions were analyzed for 5-FU content (RP-HPLC). These fractions were also administered to HCT 116 cell culture in order to investigate their anti-carcinogenic characteristics. The release of 5-FU was 98.5% complete after 30 min of dissolution in SIF. Increasing 5-FU concentrations in dissolved fractions inhibited HCT 116 viability significantly. After complete dissolution, cellular viability was approx. 2%. These results demonstrated that sunflower pectin might be utilized as a rapid release agent in drug delivery applications. © 2017, Association of Indian Pharmacist. All rights reserved.
Keywords: 5-fluorouacil (5-FU); Anti-carcinogenic activity; HCT 116; Hydrogel; Sunflower pectin